Trends and research patterns of blended learning in science education: A VOSviewer-based bibliometric analysis - Mastuang Mastuang; Misbah Misbah; Rossy Arlinda; Nurlaela Muhammad; Muhdi Harto; Qamariah Qamariah; Mazlena Binti Murshed (Journal of Environment and Sustainability Education, 2025)
Blended learning combines online and face-to-face, creating a dynamic and interactive learning environment. This article aims to provide a comprehensive bibliometric literature review on "blended learning in science learning". Articles found with the Scopus database. There are 100 out of 449 articles found in the Scopus database from 2020 to 2024 analyzed in this study. The selected references were then managed using reference management software, namely Mendeley. After managing the database, these studies classified and visualized them using VOSviewer software. The results of this study are that the distribution of authors who research topics related to blended learning in science learning is still dominated by the United States and Indonesia. The gap in this study shows the future agenda's direction: blended learning in science learning is very important to study. Overall, teaching and learning activities using blended learning in science learning tend to increase yearly. This is also needed for more inter-regional research collaborations involving researchers from Asia and other developing countries in certain areas. Overall, this review provides a good reference point for further research on "blended learning in science learning".